Economic analysis of oil palm production in the Province of Agusan del Sur - Pelpinosas, Marina D.
This study conducted to analyze the production of oil palm fresh fruit bunch in the province of Agusan del Sur from 1985 to 2000. Linear regression approach was applied to analyze the trends in the volume of production, area devoted to oil palm plantation, yield per hectare and average price of oil palm fresh fruit bunch. The Cobb-Douglas production function was utilized in determining the fitted model in the production function. Results revealed that there was an upward trend in the volume of production and yield per hectare. Trend in area increased gradually while price of fresh fruit bunch showed fluctuations. It was also found that there was a positive relationship between volume of production and the following factors: area, yield per hectare and price of fresh fruit bunch. However, there was an inverse relationship between volume of production and the following variables: prices of inputs (labor and fertilizer) and amount of rainfall. Furthermore, the study found out that production of palm oil in Agusan del Sur significantly contributed to the national production from year 1985 to 2000. Finally, the study also found that consumption of palm oil in the country depended largely in the province of Agusan del Sur. However, production in Agusan del Sur did not fully meet the demand of the country, which resulted to an increasing trend in import of palm oil. This implied that production in Agusan del Sur, and indeed in the country, was not adequate to supplement the demand of palm oil in the country.